FISH detection of chromosome polymorphism and deletions in the spinal muscular atrophy (SMA) region of 5q13 - RAJCAN-SEPAROVIC, E; MAHADEVAN, M. S; LEFEBVRE, C; BESNER-JOHNSTON, A; IKEDA, J.-E; KORNELUK, R. G; MACKENZIE, A (Cytogenetic and genome research, 1996)
The search for the SMA defect has culminated in the identification of two candidate 5q13.1 SMA genes, NAIP and SMN both of which are deleted in individuals with SMA. It was postulated that the intact and degenerate versions of NAIP are present in variable and frequently high copy numbers in this region while SMN was proposed to be present in only two copies. In order to assess the copy number of NAIP and SMN we have conducted interphase FISH analysis using NAIP and SMN gene-containing cosmid and plasmid probes. Our results confirm the variability in the number of NAIP signals in non-SMA chromosomes (2-6) and show that SMN is present on average twice per chromosome although in one chromosome 4-5 signals for the SMN-containing cosmid probe were detected. Our analysis reveals that one of four and three of six type I SMA chromosomes had a lower than normal number of NAIP and SMN signals, respectively. In two of six SMA type I chromosomes, complete loss of hybridization signal was observed on one chromosome 5 with our SMN cosmid probe possibly reflecting a large scale deletion. Large scale deletions were not detectable when metaphase chromosomes of an SMA type II and III patient were analyzed.